A secure Search over Distributed Data - J. Mohammed, Rana (Iraqi Journal of Science, 2023)
In recent years, due to the economic benefits and technical advances of cloudcomputing, huge amounts of data have been outsourced in the cloud. To protect theprivacy of their sensitive data, data owners have to encrypt their data prioroutsourcing it to the untrusted cloud servers. To facilitate searching over encrypteddata, several approaches have been provided. However, the majority of theseapproaches handle Boolean search but not ranked search; a widely acceptedtechnique in the current information retrieval (IR) systems to retrieve only the top–krelevant files. In this paper, propose a distributed secure ranked search scheme overthe encrypted cloud servers. Such scheme allows for the authorized user to searchthe distributed documents in a descending order with respect to their relevancedocuments and the contents of files be retrieved. To do so, each data owner buildsits own searchable index, and associates with each document in that index its weightscore, which facilitate document ranking. To ensure the privacy of these weights,utilized the ranking. While preserving their capability to perform the ranking processand to conducted several empirical analyses on a real dataset, all programs needed tothe propose system written using Matlab language.